2001
DOI: 10.1128/jvi.75.19.8987-8998.2001
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanism of Antiviral Action of Iminosugar Derivatives against Bovine Viral Diarrhea Virus

Abstract: The glucose-derived iminosugar derivatives N-butyl-and N-nonyl-deoxynojirimycin (DNJ) have an antiviral effect against a broad spectrum of viruses including Bovine viral diarrhea virus (BVDV). For BVDV, this effect has been attributed to the reduction of viral secretion due to an impairment of viral morphogenesis caused by the ability of DNJ-based iminosugar derivatives to inhibit ER ␣-glucosidases (N. Zitzmann, A. S. Mehta, S. Carrouée, T. D. Butters, F. M. Platt, J. McCauley, B. S. Blumberg, R. A. Dwek, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
133
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(139 citation statements)
references
References 25 publications
4
133
0
2
Order By: Relevance
“…Previous experiments have shown that the antiviral effect of the longalkyl-chain derivative N-nonyl-DNJ (NN-DNJ) is more pronounced than that of the short-alkyl-chain derivative N-butyl-DNJ (NB-DNJ), although the latter achieves a more effective ER ␣-glucosidase inhibition in cellulo. In addition, long-alkylchain DGJ derivatives that are not recognized by and do not inhibit ER ␣-glucosidases also show potent antiviral activity (3). Therefore, ER ␣-glucosidase inhibition does not correlate directly with the observed antiviral effect and is ruled out as the sole antiviral mechanism.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Previous experiments have shown that the antiviral effect of the longalkyl-chain derivative N-nonyl-DNJ (NN-DNJ) is more pronounced than that of the short-alkyl-chain derivative N-butyl-DNJ (NB-DNJ), although the latter achieves a more effective ER ␣-glucosidase inhibition in cellulo. In addition, long-alkylchain DGJ derivatives that are not recognized by and do not inhibit ER ␣-glucosidases also show potent antiviral activity (3). Therefore, ER ␣-glucosidase inhibition does not correlate directly with the observed antiviral effect and is ruled out as the sole antiviral mechanism.…”
mentioning
confidence: 99%
“…The predominant antiviral mechanism is proposed to be mediated directly or indirectly by an effect of the long-alkyl side chains on the membrane and͞or membrane proteins, because treatment with long-alkyl-chain iminosugars affects the dimerization of viral membrane glycoproteins and alters the membrane glycoprotein composition of secreted BVDV virions but does not influence either viral RNA replication or protein synthesis (3).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23] Iminosugar-based compounds are promising medicine candidates against various diseases such as tumor metastasis, diabetes, viral infection, and lysosomal storage disorders. [23][24][25] Our group discovered that certain iminosugar derivatives possess immunosuppressive activities while minor structure changes lead to immunostimulating activities, showing the potential as the lead compounds with various biological activities. [26][27][28] Two castanospermine (an iminosugar) analogues also showed up-regulation of the Th1/Th2 cytokine ratio, with apparent bias towards Th1 cytokines.…”
Section: Introductionmentioning
confidence: 99%